Seleção de medicamentos: indicadores, estratégias de implantação e contribuições para o Sistema Único de Saúde - Santana, Rafael Santos (2013)
The development of essential medicines list is one of the main policies, globally accepted, for promoting rational drug use. Despite advances in developed countries, in countries like Brazil difficulties of establishing pharmacy and therapeutics committees, as well as the maintenance of its activities are characterized as a challenge for managers of health services. This study aimed to identify indicators, strategies for implementation and impact of policies on medicines selection in public hospitals. Through an approach of evaluative research in service work is divided into three steps: 1) Exploratory Phase (initial planning of the research and literature review), 2) Field Work Phase (institutionalizing the process of medicines selection in health services using the Situational and Strategic Planning - SSP), 3) Analysis of data (measurement and processing of data collected during the study). In this study, it was possible to perform an integrative literature review that results in 45 indicators for the evaluation of drug selection in health services and to construct optimal strategies for implementation of this activity in public hospitals through the SSP. The study culminated in analysis of economic-assistance impact, establishment of DTC and definition of essential medicine lists in public hospitals.